Determination of non-methane hydrocarbon emission factors from vehicles in a tunnel in Seoul in May 2000 - Na, K; Moon, KC; Kim, YP (KOREAN INST CHEM ENGINEERS, 2002)
Measurements of non-methane hydrocarbons (NMHC) were performed at the entrance and exit of the Sangdo tunnel to estimate emission factors (EF) of NMHC from vehicles in May 2000. About 50 species were analyzed by a combined GC/FID and GC/MS system. Ethylene was the most abundant compound, followed by n-butane and acetylene, respectively. Based on the measurement data, the real world vehicular EF in Seoul was estimated. The highest EF value was 89.8 mg (veh-mile)(-1) for n-butane, followed by ethylene and toluene.
Keywords: ORGANIC-COMPOUNDS; ROAD; AREA